GmEXLB1, a Soybean Expansin-Like B Gene, Alters Root Architecture to Improve Phosphorus Acquisition in Arabidopsis - Kong, Youbin; Wang, Bing; Du, Hui; Li, Wenlong; Li, XiHuan; Zhang, Caiying (Frontiers in Plant Science, 2019)
Expansins comprise four subfamilies, α-expansin (EXPA), β-expansin (EXPB), expansin-like A (EXLA) and expansin-like B (EXLB), which are involved in the regulation of root development and growth under abiotic stress. To date, few EXLB genes have been shown to respond to low phosphorus (P) in plants. In this study, we identified an EXLB gene, GmEXLB1, by analyzing the transcription profiles of GmEXLBs in soybean. Quantitative analysis showed that GmEXLB1 was expressed and induced in the lateral roots of soybean under low P conditions. The observation of β-glucuronidase staining in transgenic Arabidopsis suggested that GmEXLB1 might be associated with lateral root emergence. GmEXLB1 overexpression altered the root architecture of transgenic Arabidopsis by increasing the number and length of lateral roots and the length of primary roots under low P conditions. Additionally, the length of the elongation zone and the average cell length in the elongation zone were increased in transgenic Arabidopsis. Increases in biomass and P content suggested that GmEXLB1 overexpression enhanced P acquisition in Arabidopsis. Overall, we conclude that GmEXLB1 expression is induced in soybean under low P conditions, and the overexpression of GmEXLB1 improves P acquisition by regulating root elongation and architecture in Arabidopsis, which provides a possible direction for research of the function of this gene in soybean.